Lyndon B. Johnson and the Civil Rights Act - Lüsted, Marcia Amidon (Spotlight on the civil rights movement., 2018)
Explores the work President Lyndon B. Johnson did in order to get the Civil Rights Act of 1964 to pass and become a law in America.